Metabolic fate of desomorphine elucidated using rat urine, pooled human liver preparations, and human hepatocyte cultures as well as its detectability using standard urine screening approaches - Richter, Lilian; Meyer, Markus Robert (Analytical and bioanalytical chemistry, 2016)
Desomorphine is an opioid misused as “crocodile”, a cheaper alternative to heroin. It is a crude synthesis product homemade from codeine with toxic byproducts. The aim of the present work was to investigate the metabolic fate of desomorphine in vivo using rat urine and in vitro using pooled human liver microsomes and cytosol as well as human liver cell lines (HepG2 and HepaRG) by Orbitrap-based liquid chromatography-high resolution-tandem mass spectrometry or hydrophilic interaction liquid chromatography. According to the identified metabolites, the following metabolic steps could be proposed: N-demethylation, hydroxylation at various positions, N-oxidation, glucuronidation, and sulfation. The cytochrome P450 (CYP) initial activity screening revealed CYP3A4 to be the only CYP involved in all phase I steps. UDP-glucuronyltransferase (UGT) initial activity screening showed that UGT1A1, UGT1A8, UGT1A9, UGT1A10, UGT2B4, UGT2B7, UGT2B15, and UGT2B17 formed desomorphine glucuronide. Among the tested in vitro models, HepaRG cells were identified to be the most suitable tool for prediction of human hepatic phase I and II metabolism of drugs of abuse. Finally, desomorphine (crocodile) consumption should be detectable by all standard urine screening approaches mainly via the parent compound and/or its glucuronide assuming similar kinetics in rats and humans.